Profissão e formação do arquiteto na era digital: proposta de complexo de arquitetura e urbanismo para a UFPA. - ALVARES, Luiz Felipe Estrella (2023)
From the study of the profession and the teaching of architecture in the current digital age, this work proposes the elaboration of a project for a complex of architecture and urbanism within the Federal University of Pará. It seeks to observe the progress from the industrial revolutions, to understand how they relate to teaching, understanding how industry is linked not only with the profession but also with what is taught in universities. In this evolution, it is proposed to reach the present moment of the fourth industrial revolution, where the advent of new technologies proceed at a very fast frequency, which requires adaptation and flexibility from the teaching spaces. The proposed project then seeks to organize the information collected for the elaboration of a architectural program coherent with the space in which the intervention will take place and with the digital age, establishing a discussion about a quality teaching space